Pemanfaatan Media Vidio Edukasi Sebagai Upaya Pencegahan Kejadian Stunting Pada Balita Di Posyandu Flamboyan - Suryati Suryati; Noor Anisa; Rr, Nuriaty Masdiputri; Ida Fithriyani; Gita Wulanda Sari (UrbanGreen, 2023)
Video is a type of audio-visual based learning media that stimulates the functioning of the sense of hearing and sight. Videos can be used to provide education to pregnant and breastfeeding mothers to prevent stunting in toddlers. The results of the study showed that there was a difference in the average knowledge about efforts to prevent stunting in toddlers before and after being given education using videos about efforts to prevent stunting in toddlers. In conclusion, providing health education using videos about efforts to prevent stunting in toddlers can increase the knowledge of pregnant and breastfeeding mothers about efforts to prevent stunting in toddlers